Hubungan Durasi Kerja, Masa Kerja, dan Penggunaan Alat Pelindung Diri terhadap Faal Paru pada Pekerja Penyortir Bawang Merah - Nila Nurdiana N; Susilo Budi Pratama; Nabil Hajar; Muslimah, Muslimah (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2025)
Data from the International Labor Organization (ILO) in 2018 states that 270 million workers experience work-related accidents every year. Agricultural industry workers are vulnerable to exposure to dust in the work environment, which can cause lung function problems. If dust is present in excessive amounts for a long period of time, it can cause pathological damage to humans making them susceptible to disease, especially pneumoconiosis. The aim of this study was to analyze the relationship between work duration, length of service, and use of personal protective equipment on lung function in shallot sorting workers. This research method is quantitative observational analytic using a cross sectional design. This study used a questionnaire and spirometry examination. The sample for this research was red onion sorting workers in Tawangharjo Village who were taken using total sampling. Data analysis used the chi square correlation test. The total sample that met the inclusion criteria was 45 respondents. The results of the chi square correlation test showed p<0.05, which means there is a significant relationship between work duration, work period, and use of personal protective equipment on lung function. There is a significant relationship between work duration, length of service, and use of personal protective equipment on lung function in shallot sorting workers.